Embedding a membrane protein into an enveloped artificial viral replica. Issue 2 (4th January 2022) - Furukawa, Hiroto; Inaba, Hiroshi; Sasaki, Yoshihiro; Akiyoshi, Kazunari; Matsuura, Kazunori
Abstract : We demonstrate the embedding membrane protein, Cx43, on the enveloped artificial viral capsid using a cell-free expression system. The embedding of Cx43 on the envelope was evaluated by detection with anti-Cx43 antibody using FCS and TEM. Abstract : Natural enveloped viruses, in which nucleocapsids are covered with lipid bilayers, contain membrane proteins on the outer surface that are involved in diverse functions, such as adhesion and infection of host cells. Previously, we constructed an enveloped artificial viral capsid through the complexation of cationic lipid bilayers onto an anionic artificial viral capsid self-assembled from β-annulus peptides. Here we demonstrate the embedding of the membrane protein Connexin-43 (Cx43), on the enveloped artificial viral capsid using a cell-free expression system. The expression of Cx43 in the presence of the enveloped artificial viral capsid was confirmed by western blot analysis. The embedding of Cx43 on the envelope was evaluated by detection via the anti-Cx43 antibody, using fluorescence correlation spectroscopy (FCS) and transmission electron microscopy (TEM). Interestingly, many spherical structures connected to each other were observed in TEM images of the Cx43-embedded enveloped viral replica. In addition, it was shown that fluorescent dyes could be selectively transported from Cx43-embedded enveloped viral replicas into Cx43-expressing HepG2 cells. This study provides a proof of concept for the creation of multimolecular crowding complexes, that is, an enveloped artificial viral replica embedded with membrane proteins.